2021
DOI: 10.3390/v13071409
|View full text |Cite
|
Sign up to set email alerts
|

Previous Usutu Virus Exposure Partially Protects Magpies (Pica pica) against West Nile Virus Disease But Does Not Prevent Horizontal Transmission

Abstract: The mosquito-borne flaviviruses USUV and WNV are known to co-circulate in large parts of Europe. Both are a public health concern, and USUV has been the cause of epizootics in both wild and domestic birds, and neurological cases in humans in Europe. Here, we explore the susceptibility of magpies to experimental USUV infection, and how previous exposure to USUV would affect infection with WNV. None of the magpies exposed to USUV showed clinical signs, viremia, or detectable neutralizing antibodies. After challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 47 publications
0
10
1
Order By: Relevance
“…Currently, there is little evidence in immune enhancement of disease severity or virus infectivity between WNV and USUV infections. In contrast, cross-protection against WNV by prior USUV immunity was previously reported [50], and our study reports the first animal experiment data showing cross-protection against USUV illness by WNV vaccination.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Currently, there is little evidence in immune enhancement of disease severity or virus infectivity between WNV and USUV infections. In contrast, cross-protection against WNV by prior USUV immunity was previously reported [50], and our study reports the first animal experiment data showing cross-protection against USUV illness by WNV vaccination.…”
Section: Discussioncontrasting
confidence: 70%
“…For instance, both WNV-and USUV-specific neutralizing antibodies were detected in migratory and resident birds in eastern Germany [53]. Recently, it was shown that magpies previously exposed to USUV are partially protected from WNV, indicated by higher survival rates post-WNV challenge [50]. The interactions between WNV and USUV in mosquito vectors and avian hosts will be critical to monitor as WNV and USUV continue to emerge.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing circulation of USUV would have important implications on WNV as it would affect human health and potentially convoluting diagnostics. USUV may have a strong cross-neutralizing potential towards WNV; the two closely related flaviviruses of the JEV serocomplex cannot persist in the same ecological niche due to cross-protective avian herd immunity [ 51 ]. Furthermore, Cx .…”
Section: Discussionmentioning
confidence: 99%
“…An increasing circulation of USUV would have important implications on WNV as it affects significantly human health. USUV may have a strong cross-neutralizing potential towards WNV; the two closely related flaviviruses of the JEV serocomplex cannot persist in the same ecological niche due to cross-protective avian herd immunity (51). Furthermore, Cx.…”
Section: Introduction Of Wnv In Mainlandmentioning
confidence: 99%